Strategi Peningkatan Profesionalisme Guru Pendidikan Agama Buddha di Daerah Terpencil - Melva Audina; Partono Partono (Journal of Literature Review, 2026)
This article is a systematic literature review (SLR) that review examines research on “Strategies for Enhancing the Professionalism of Buddhist Religious Education Teachers in Remote Areas” to address challenges in enhancing teacher professionalism in the context of distance Buddhist education. The review aims to evaluate strategies for enhancing professionalism, benchmark technology-enabled and community-based initiatives, identify challenges, compare pedagogical approaches, and analyze institutional and policy influences. A systematic analysis of qualitative, quantitative, and mixed-methods studies from Indonesia and comparable rural areas is conducted, focusing on interventions from the past two decades. Findings indicate that blended and AI-assisted training programs significantly improve teacher competency and pedagogical skills, while persistent infrastructure limitations and digital literacy gaps limit technology integration. Community and professional learning networks effectively reduce isolation and foster collaboration, although sustained engagement requires stronger institutional support. Pedagogical innovations, including mindful communication and digital literacy frameworks, improve teaching quality but often face challenges in practical application and contextual adaptation. Institutional and policy factors critically influence program sustainability, with funding, infrastructure, and policy alignment identified as key determinants. These findings converge to underscore the need for sustainable and context-sensitive strategies that integrate technological, sociocultural, and institutional dimensions. This review informs policy development and training program design aimed at promoting equitable and effective professional development for Buddhist education teachers in geographically villages areas.